Life cycle analysis of an alternative to the haber-bosch process: Non-renewable energy usage and global warming potential of liquid ammonia from cyanobacteria - Razon, Luis F. (Animo Repository, 2014)
The production of ammonia via the Haber-Bosch process consumes large amounts of fossil fuels and releases large amounts of greenhouse gases. Ammonia has many important applications including fertilizer for crops and for microalgae-derived biofuel systems. Aquatic cyanobacteria fix nitrogen from the air and have been mass-cultured for many uses. This study analyzes, on a life cycle basis, a process to culture the cyanobacterium, Anabaena sp. ATCC 33047, in open ponds; harvest the biomass and exopolysaccharides and convert these to biogas; strip and convert the ammonia from the biogas residue to ammonium sulfate; dry the ammonium sulfate solution to ammonium sulfate crystals; transport the ammonium sulfate and convert it to liquid ammonia and concentrated sulfuric acid. When compared to the ammonia produced via the Haber-Bosch process, savings of about 1.0 × 105 MJ of non-renewable energy and 3100 kg CO2 equivalent of global warming potential per 1000 kg of liquid ammonia might be possible. The results are robust and are not sensitive to the model parameters. The proposed system, if implemented, might have a significant impact on many important global issues such as global warming, fossil fuel depletion, and food security. © 2013 American Institute of Chemical Engineers Environ Prog, 33: 618-624, 2014 © 2013 American Institute of Chemical Engineers Environ Prog.